The Related Variables and the Reading Proficiency Level of Grade Six Pupils - Maleon, Jeremie Monter (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2022)
This study describes the relationship between the respondents’ reading proficiency level as demonstrated in their Lexile Scores and the following variables: Respondent- related Factors, Teacher Factors, School Factors, and Home Factors. The Theory of Performance (ToP) by Don Elger served as the basis to develop the research instrument, i.e., survey questionnaire. Seventy (70) grade six pupils were authorized by a private school in the Philippines to become the respondents of the study. Correlated with the aforementioned factors were the pupils’ reading Lexile Scores provided by Scholastic Philippines. The data were processed through the SPSS software using the Pearson Product- Moment Correlation Coefficient formula. Results revealed that among the four sets of factors, only Home Factors have a significant relationship with the Lexile Scores of the respondents. Furthermore, specific factors such as gender and mother’s occupation relate with the pupils’ reading proficiency level.